2018
DOI: 10.1016/j.ecoenv.2017.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity assessment of dicationic versus monocationic ionic liquids as a more environmentally friendly alternative

Abstract: One of the reasons why ionic liquids have received growing interest from researchers is their environmentally interesting characteristics, such as their negligible vapour pressure and their good chemical and thermal properties. In particular, dicationic ionic liquids whose thermal and electrochemical stability is higher than that of monocationic ionic liquids have begun to gain attention during recent years. In this work, monocationic and dicationic ionic liquids were synthesized, characterized and tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…Table 2 also shows the octanol-water partition coefficients estimated from the Eq. 1, proposed by Montalbán et al [36]: , has the lowest toxicity among all the studied ILs, which is in good agreement with previous studies [37,38]. It is interesting to highlight that the effect of the anion on the toxicity decreases with longer cation alkyl chains.…”
Section: Resultssupporting
confidence: 89%
“…Table 2 also shows the octanol-water partition coefficients estimated from the Eq. 1, proposed by Montalbán et al [36]: , has the lowest toxicity among all the studied ILs, which is in good agreement with previous studies [37,38]. It is interesting to highlight that the effect of the anion on the toxicity decreases with longer cation alkyl chains.…”
Section: Resultssupporting
confidence: 89%
“…A few works indicated that DILs behave in a different way from the structurally related MILs when tested in the same application. For instance, it has been found that some DILs are characterized by lower polarity and different structural organizations, 21 higher thermal stabilities, 22 lower ecotoxicities, 23 higher activity in the cycloaddition of CO 2 to epoxides, 24 higher or lower cathodic reductions, depending on the type of spacer. 25 The physico-chemical properties of ILs, and accordingly their potential applications, are strictly governed by the type and strength of the interaction between the constituent ions.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and orientation of cations are key factors that determine membrane interactions and concurrent toxicity to different microorganisms. While an increase in the cationic side chain length of an IL is directly related to an increase in membrane activity, the orientation of the cationic group emerges as a structural and biological element that must be considered in ILs toxicity . The most amino acid ILs (AAILs) were found to be nontoxic with no inhibition zone against target bacteria, while some AAILs demonstrated low toxicity even at high concentrations (1 mol L −1 ) .…”
Section: Toxicity Of Ionic Liquids Toward Microorganismsmentioning
confidence: 99%
“…They have remarkable features that can be easily custom‐made by a plethora of cations and anions, making them task‐specific solvents and agents. Because of these tailor‐made properties, ILs have been used in a wide variety of applications including biotechnology, chemical engineering, separation processes, material sciences, green chemistry, pharmaceutics, and many others. The use of ILs in biological applications has gained popularity in recent years because ILs are less toxic than that of many conventional organic solvents.…”
Section: Introductionmentioning
confidence: 99%